THE LINK BETWEEN NUTRIENT INTAKE AND PREECLAMPSIA INCIDENCE IN PREGNANT WOMEN AT PUSKESMAS UMBULHARJO 1 YOGYAKARTA - Dyah Suryani; Ram Famelia; Maretalinia Maretalinia (Fakultas Ilmu Kesehatan, Universitas Ibn Khaldun, Bogor, 2026)
This study addresses the relatively high maternal mortality rate in Indonesia, where in 2023 there were 4,460 cases, with hypertension during pregnancy as a leading cause. It aims to examine the relationship between nutrient intake, maternal age, parity, and nutritional status and the incidence of preeclampsia at Umbulharjo 1 Public Health Center in Yogyakarta. Using a quantitative cross-sectional design, the study involved 45 respondents selected through accidental sampling based on Slovin’s formula, with data collected באמצעות the Semi-Quantitative Food Frequency Questionnaire (SQFFQ). The findings revealed that 33.3% of respondents experienced preeclampsia, with most showing inadequate intake of protein, fat, carbohydrates, sodium, and potassium, but relatively adequate fiber intake. The majority were within the non-risk maternal age group, had low-risk parity, and exhibited poor nutritional status. Bivariate analysis using Fisher’s exact test indicated significant associations between preeclampsia and fat intake, fiber intake, sodium intake, maternal age, parity, and nutritional status, while no significant relationships were found with protein, carbohydrate, or potassium intake. Overall, the study concludes that several nutritional and maternal factors are significantly linked to the occurrence of preeclampsia, highlighting the importance of dietary and maternal health considerations in its prevention.